2019
DOI: 10.1038/s41598-019-39161-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of isomeric plastomes and effectiveness of plastome super-barcodes in yews (Taxus) worldwide

Abstract: Taxus (yew) is both the most species-rich and taxonomically difficult genus in Taxaceae. To date, no study has elucidated the complexities of the plastid genome (plastome) or examined the possibility of whole plastomes as super-barcodes across yew species worldwide. In this study, we sequenced plastomes from two to three individuals for each of the 16 recognized yew species (including three potential cryptics) and Pseudotaxus chienii . Our comparative analyses uncovered severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 74 publications
0
81
1
Order By: Relevance
“…Our results indicated that, for those species (P. stipuleanatus, P. ginseng, P. quinquefolius and P. notoginseng) whose monophyly has been recognized by previous studies (Zuo et al, 2011(Zuo et al, , 2017 (Coissac et al, 2016;Kan & Cronk, 2008;Kane et al, 2012;Li et al, 2015;Nock et al, 2011;Tontifilippini et al, 2017), although the efficiency of this approach still lacks comprehensive evaluation. Furthermore, (Kane et al, 2012) and Taxus (Fu et al, 2019). However, they failed to fully identify species in Panax (the current study) and New Caledonian Araucaria (Ruhsam et al, 2015), even though there are some gains in discriminatory power.…”
Section: Implications For Dna Barcodingcontrasting
confidence: 59%
See 3 more Smart Citations
“…Our results indicated that, for those species (P. stipuleanatus, P. ginseng, P. quinquefolius and P. notoginseng) whose monophyly has been recognized by previous studies (Zuo et al, 2011(Zuo et al, , 2017 (Coissac et al, 2016;Kan & Cronk, 2008;Kane et al, 2012;Li et al, 2015;Nock et al, 2011;Tontifilippini et al, 2017), although the efficiency of this approach still lacks comprehensive evaluation. Furthermore, (Kane et al, 2012) and Taxus (Fu et al, 2019). However, they failed to fully identify species in Panax (the current study) and New Caledonian Araucaria (Ruhsam et al, 2015), even though there are some gains in discriminatory power.…”
Section: Implications For Dna Barcodingcontrasting
confidence: 59%
“…Furthermore, the discriminatory power revealed by previous studies sampling multiple intraspecific individuals from multiple congeneric species is largely incongruent. For instance, either complete plastomes or nrDNA sequences were shown to successfully distinguish closely related species in Theobroma (Kane et al, ) and Taxus (Fu et al, ). However, they failed to fully identify species in Panax (the current study) and New Caledonian Araucaria (Ruhsam et al, ), even though there are some gains in discriminatory power.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For plastomic studies, genetic analyses using plastome fragments have been conducted to reconstruct the phylogeny of the Taxaceae family (e.g., Ran et al, 2010), to develop barcodes to differentiate different species (Gao et al, 2017;Liu et al, 2018), and to explore the demographic history of certain species or species complexes (Ge et al, 2015;Su et al, 2018). Recently, several groups released a number of Taxaceae plastomes Tao et al, 2016;Jia and Liu, 2017), and both intraspecific and interspecific isomeric arrangements have been reported (Hsu et al, 2014;Fu et al, 2019). However, the relative location and genomic organization of the inverted f r a g m e n t s i n T a x a c e a e p l a s t o m e s h a v e n o t b e e n comprehensively studied yet.…”
Section: Introductionmentioning
confidence: 99%